A Grounded Theory Exploration of the Dimensions of Assessment Fairness From Teachers’ Perspectives - Jafari-Nezhad , Hanieh; Mohaghegh, Salar (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore how secondary school teachers conceptualize and enact assessment fairness within their professional practice, using a grounded theory approach. This qualitative study employed a grounded theory design to investigate perceptions of assessment fairness among secondary school teachers in Tehran. Data were collected through semi-structured interviews with 20 participants, selected using purposive sampling to ensure diversity in gender, teaching discipline, and school type. Interviews continued until theoretical saturation was achieved. All interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo software. Data analysis followed the constant comparative method, including open, axial, and selective coding to identify categories and develop a theoretical model grounded in participants’ experiences. Analysis revealed three major dimensions of assessment fairness from teachers' perspectives: procedural fairness, interpersonal fairness, and distributive fairness. Procedural fairness encompassed elements such as transparent criteria, consistency in grading, alignment with learning objectives, and appeal mechanisms. Interpersonal fairness involved respectful communication, cultural sensitivity, positive teacher–student relationships, and equal opportunity for expression. Distributive fairness highlighted equity in grading, accommodation for contextual barriers, rewarding individual progress, and avoidance of peer comparison. Teachers described fairness as a complex, context-sensitive construct that required ethical judgment, flexibility, and relational awareness. The study offers a comprehensive grounded theory model of assessment fairness that integrates ethical, pedagogical, and relational dimensions. It challenges narrow, standardized definitions of fairness and underscores the importance of teacher agency in navigating fairness dilemmas. These findings have implications for assessment policy, teacher education, and equity-focused instructional practice.